KOMUNIKASI SINGKAT: KEBIASAAN MAKAN IKAN KEPALA TIMAH (Aplocheilus panchax, Hamilton 1822) DI PERAIRAN EKSTREM ASAM PASCATAMBANG TIMAH TERABAIKAN - Diah Mustikasari; andri kurniawan; Bima Syifa Aznur (Jurusan Akuakultur, Universitas Bangka Belitung, 2023)
Kepala Timah (Aplocheilus panchax, Hamilton 1822) is one of the fish that has the survival abilities to live in a wide variety of quality waters. The ability of A. panchax to survive in acidic waters has begun to be widely studied as extremophile fish to study ecosystems in aquatic habitats that have acidic characteristics. This study aimed to determine the food habits of A. panchax as natural food in acid water of abandoned ex-tin mining activity. The results showed that the natural food for A. panchax was insects larvae or insects that fall on the surface of the waters. The food habits and terminal mouth type confirmed that A. panchax was surface feeder fish, carnivorous fish, larvivorous or insectivorous fish. The sagittiform body type was used A. panchax to did the strategy of feeding behavior by pursue or ambush their prey and it indicated that A. panchax as ambush predator.